Immediate effects of water resistance therapy on patients with vocal fold mass lesions - Echternach, Matthias; Raschka, Julius; Kuranova, Liudmila; Köberlein, Marie; Richter, Bernhard; Döllinger, Michael; Kainz, Marie Anne (European Archives of Oto-Rhino-Laryngology, 2020)
Introduction: Semi-occluded vocal tract exercises, such as water resistance therapy (WRT), are widely used in voice therapy. However, the potential positive effects of such a therapy on vocal fold oscillation patterns in patients indicating a need for phonomicrosurgery have not yet been explored. The presented study aims to analyze the effect of WRT in patients suffering from vocal fold mass lesions. Materials and methods: Eight participants with vocal fold mass lesions were asked to sustain a phonation on the vowel /i/ at a comfortable loudness and a fundamental frequency of 250 Hz (females) or 125 Hz (males). During phonation the subjects were simultaneously recorded with transnasal high-speed videoendoscopy (HSV, 20.000 fps), electroglottography, and audio signals. These subjects then performed a WRT (phonation in a silicone tube of 30 cm length, 5 cm below the water surface) for 10 min. Repeated measurements of sustained phonation were performed 0, 10, and 30 min after exercising. From the HSV data the glottal area waveform (GAW) was segmented and GAW parameters were computed. Results: During WRT there was an increase of the GAW related open quotient and closing quotient. Immediately after WRT, there was a drop of both values followed by a rise of these parameters up to 30 min after the intervention. Furthermore, there was no correlation between GAW and electroglottographical open quotients. Conclusions: The effects observed after a single session of WRT on participants with vocal fold mass lesions showed a similar pattern to vocal fatigue.
CRIS-Team Scopus Importer:2020-03-27
Keywords: EGG; High-speed imaging; Vocal fold mass lesion; Water resistance therapy